Ultra-High Performance Liquid Chromatography Method Validation for Micro-dissolution Analysis of Ketoconazole in Alginate-Acacia Gum Composite Capsules - Lumakso, Fajar Aji; Annisa, Viviane; Cermenda, Riska; Chabib, Lutfi (Journal of Food and Pharmaceutical Sciences, 2025)
Ketoconazole, a BCS Class 2 antifungal drug, has good absorption but suffers from low solubility and poor bioavailability. To address this, a natural polymer-based matrix of alginate and acacia gum was formulated to enhance dissolution. This study aimed to validate a Ultra High Performance Liquid Chromatography method for analyzing ketoconazole content in micro-dissolution testing of capsule formulations. The method employed a C18 column with a mobile phase of acetonitrile:WFI (0.15% TEA, pH 3.5; 50:50) at 1 mL/min and detection at 265 nm. Validation demonstrated compliance with selectivity, linearity (r = 0.9996), sensitivity (LoD 6.51 µg/mL; LoQ 19.74 µg/mL), accuracy (99.6–101.3%), and precision (<2%, except one interday result at 2.08%). Micro-dissolution testing showed sustained ketoconazole release, exceeding 100% within 240 minutes. Data modeling (performed using DDSolver) indicated comparable fit for the Higuchi (R²_adj = 0.96) and Korsmeyer (R²_adj = 0.93) models, suggesting diffusion-controlled release of ketokonazole. The validated UHPLC method is suitable for micro-dissolution studies, and the alginate-acacia gum formulation effectively modulates drug release.